2000
DOI: 10.1074/jbc.275.7.5011
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Hormone-sensitive Lipase and Perilipin upon Lipolytic Stimulation of Rat Adipocytes

Abstract: Adipocyte lipolysis was compared with hormone-sensitive lipase (HSL)/perilipin subcellular distribution and perilipin phosphorylation using Western blot analysis. Under basal conditions, HSL resided predominantly in the cytosol and unphosphorylated perilipin upon the lipid droplet. Upon lipolytic stimulation of adipocytes isolated from young rats with the ␤-adrenergic agonist, isoproterenol, HSL translocated from the cytosol to the lipid droplet, but there was no movement of perilipin from the droplet to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
3
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(180 citation statements)
references
References 35 publications
9
160
3
7
Order By: Relevance
“…The localized metabolic subdomain is consistent with a small cytosolic volume due to large lipid droplet in adipocyte (Moore et al, 2005;Denton et al, 1966). Furthermore, the volume fraction of this metabolic subdomain estimated by the model corresponds to the volume fraction of intracellular water space (1~4% of total tissue volume) measured from in vitro studies of adipose fat pad (Denton et al, 1966;Crofford and Renold, 1965) Recent in vitro studies of adipocyte lipid mobilization showed that major lipolytic enzymes and proteins are co-localized in a subcellular domain during beta-adrenergic stimulation (Granneman et al, 2007;Moore et al, 2005;Clifford et al, 2000). The localization of enzyme complexes reduces the transit time of metabolites which allows faster cellular dynamics (Welch and Easterby, 1994).…”
Section: Intracellular Compartmentationsupporting
confidence: 65%
See 1 more Smart Citation
“…The localized metabolic subdomain is consistent with a small cytosolic volume due to large lipid droplet in adipocyte (Moore et al, 2005;Denton et al, 1966). Furthermore, the volume fraction of this metabolic subdomain estimated by the model corresponds to the volume fraction of intracellular water space (1~4% of total tissue volume) measured from in vitro studies of adipose fat pad (Denton et al, 1966;Crofford and Renold, 1965) Recent in vitro studies of adipocyte lipid mobilization showed that major lipolytic enzymes and proteins are co-localized in a subcellular domain during beta-adrenergic stimulation (Granneman et al, 2007;Moore et al, 2005;Clifford et al, 2000). The localization of enzyme complexes reduces the transit time of metabolites which allows faster cellular dynamics (Welch and Easterby, 1994).…”
Section: Intracellular Compartmentationsupporting
confidence: 65%
“…The reaction rate coefficients are related by a thermodynamic constraint (or Haldane relationship): (7) In the blood compartment, the breakdown of TG to FAs and glycerol is the only reaction that is catalyzed by LPL. Since some LPL is carried by blood (Karpe et al, 1998), the activity of LPL reaction depends on adipose blood flow: (8) where K m,LPL and K m,Q are phenomenological M-M constants for the LPL reaction.…”
Section: Metabolic Fluxmentioning
confidence: 99%
“…In vivo, lipolysis is determined both by intrinsic lipase capacity and by access of lipase(s) to TAGs of the lipid droplet. This has been elegantly demonstrated for HSL, which displaces from cytosol to the lipid droplet surface following ␤-adrenergic stimulation, a process that involves protein kinase A-mediated HSL phosphorylation (21). A reciprocal displacement is observed for perilipin A, a protein that coats the lipid droplet surface and that may form a barrier to access by lipases to their TAG substrate (22).…”
Section: Discussionmentioning
confidence: 93%
“…19 Phosphorylation of HSL by protein kinase A is accompanied by translocation of HSL from the adipocyte cytosol to the surface of the lipid droplet 20 and also by phosphorylation of perilipin, a protein that appears to coat the lipid droplet and to move away upon stimulation, to allow HSL access. 20 Acute activation of lipolysis, via perilipin and HSL phosphorylation, may be brought about by catecholamines acting through b-adrenergic receptors, although in the situation of overnight fasting, when lipolysis increases steadily, b-adrenergic stimulation appears not to be involved; 21 progressive removal of insulin inhibition may be more important. Overnight secretion of growth hormone 22 and the morning rise in cortisol 23 play additional modulatory roles.…”
Section: Regulation Of Fat Storesmentioning
confidence: 99%